Evaluation of a community pharmacy-led test-and-treat service for women with uncomplicated lower urinary tract infection in England. Issue 1 (12th March 2020) - Thornley, Tracey; Kirkdale, Charlotte L; Beech, Elizabeth; Howard, Philip; Wilson, Peter
Abstract: Background: Uncomplicated lower urinary tract infections (UTIs) are common in women consulting primary healthcare, taking up GP resources. Delayed consultation can increase the risk of serious infections such as pyelonephritis or bacteraemia. Objectives: To evaluate the effectiveness and uptake of a lower UTI test-and-treat service for women presenting with urinary symptoms within a community pharmacy in supporting self-care and appropriate use of antibiotics and reducing demand on other NHS resources. Methods: The service was aligned to national guidelines to diagnose and treat lower UTI in women aged 16–64 years and used national resources to provide safety-netting and self-care advice. Consultation included clinical assessment and a urine dipstick test alongside a novel smartphone app, with diagnosis informed by test results. Women were provided with safety-netting advice and either advised on self-care, supplied with antibiotics or referred to their GP. Results: Data were analysed for 764 women who presented to 23 pharmacies during December 2018 to April 2019. Lower UTI was found to be likely in 372/496 (75.0%) women, most of whom purchased antibiotics on the same day. Had the service not been available, approximately three-quarters of women who had completed the service and responded to the question would have visited their GP (214/301) and more than one-third would have used self-care with or without going to see their GP (116/301). Conclusions: A community pharmacy-led UTI test-and-treat service for women aged 16–64 years presenting with urinary symptoms provided accessible and timely care aligned to national guidance, with 75.0% of consultations requiring antibiotic treatment.